Prevalence and persistence of SARS-CoV2 antibodies among healthcare workers in Oman - Khalid Al-Naamani; Issa Al-Jahdhami; Wafa Al-Tamtami; Kawther Al-Amri; Murtadha Al-Khabori; Siham Al Sinani; Elias A. Said; Heba Omer; Hamad Al-Bahluli; Saada Al-Ryiami; Saleh Al-Hakmani; Najat Al-Naamani; et al. (Elsevier, 2021)
Objectives: The primary objective is to determine the prevalence of SARS-CoV-2 antibodies persistence among HCWs and specifically among asymptomatic HCWs. A secondary objective is to determine the duration of persistent SARS-CoV-2 antibodies post infection and factors affecting this duration. The findings are expected to open the door for further research into the role of SARS-CoV-2 antibodies during the current COVID-19 pandemic. Methodology: HCWs were divided into high, intermediate, and low risk based on their type and location of work. All participants filled a questionnaire. Blood samples were obtained for SARS-CoV-2 IgG/total antibodies. A documented SARS-CoV-2 PCR or Anti-SARS-CoV-2 IgG/total antibodies defined the primary outcome. The probability of persistence of antibody was calculated using the Kaplan-Meier estimator. Logistic and Cox regression were used where appropriate. Results: A total of 1111 HCWs were included. The median age 37 years (IQR: 31-43). More than half (67.2%) were females. The primary outcome was seen in 373 (33.6%) participants with a median age of 36 years (IQR: 29-41). Only 37.2% of those with documented positive SARS-CoV-2 PCR had reactive serology, while only 16.2% of those with reactive serology had documented positive SARS-CoV-2 PCR. Male gender (OR 0.44, P < 0.001) and older age (OR 0.98, P < 0.019) were associated with a lower risk of acquiring SARS-CoV-2 infection. The probability of persistent SARS-CoV-2 antibodies at six months was 60.2% (95% CI: 49.5%-73.1%). Omanis had a higher probability of losing the antibody than others (HR 2.63, P = 0.021). Conclusion: We report a high prevalence of anti-SARS-CoV-2 antibodies among HCWs in Oman, specifically among asymptomatic HCWs. Community was the most likely source of infection. Therefore, the society must adhere to the roles and regulations set to reduce the risk of transmission. We demonstrate a high percentage of seroconversion post initial infection, and the persistence of SARS-CoV-2 antibodies at six months in more than half of those previously infected. We demonstrated a new interesting finding of fast decline of SARS-CoV2 antibody levels over time among different nationalities and this requires further research.